A Comparative Analysis of Artificial Intelligence Regulatory Law in Asia, Europe, and America - Alfiani Francisca Romana Nanik; Santiago Faisal (SHS Web of Conferences)
This research aims to provide a comprehensive overview of the key considerations for formulating Artificial Intelligence (AI) regulations in Asia, Europe, and America. The study employs normative research, which in this context focuses on analyzing legal frameworks, principles, and regulations governing AI. Data collection techniques include the study of legal documents such as laws and regulations, along with a qualitative analysis using comparative methods. The result of research shown that technological advances are impacting human life at an unprecedented rate. AI has become integral to various sectors, transforming industries, fuelling innovation, and reshaping the way people live and work. However, the rapid rise of AI also raises significant moral, legal, and social concerns. In response, countries like China, Indonesia, the European Union, and the United States have enacted regulations to address these issues. The primary considerations in formulating these regulations include ethical principles, data privacy, algorithmic bias, transparency, explainability, and international collaboration. While the regulatory approaches differ across these regions, they share a common goal: ensuring that AI benefits society while minimizing negative impacts.